2009
DOI: 10.1158/1055-9965.epi-08-0691
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Overexpression of Mitotic Regulatory Proteins in Biliary Tract Cancer: Correlation with Clinicopathologic Features and Patient Survival

Abstract: Mitosis dysregulation is common in cancers. This study explored the nuclear expression patterns and prognostic significance of mitotic regulatory proteins, including Aurora kinases, survivin, and p53, in biliary tract cancer (BTC). Archival tumor samples from 161 BTC patients who underwent surgery were tested for the expression of Aurora-A, Aurora-B, survivin, and p53 by immunohistochemistry. The potential endogeneity among the clinicopathologic variables and survival outcome was assessed by a generalized simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 40 publications
3
8
0
Order By: Relevance
“…The multivariate analysis confirmed that Aurora B overexpression was an independent risk factor associated with ETR (OR, 4.679; P = 0.0011; Table 2). These findings are consistent with the correlation of Aurora B overexpression with poor tumor differentiation and worse patient survival in thyroid [32], prostate [33], and hepatobiliary cancers [34,35]. Taken together, our findings suggest that Aurora B overexpression serves as a useful marker predicting ETR and hence poor prognosis.…”
Section: Discussionsupporting
confidence: 90%
“…The multivariate analysis confirmed that Aurora B overexpression was an independent risk factor associated with ETR (OR, 4.679; P = 0.0011; Table 2). These findings are consistent with the correlation of Aurora B overexpression with poor tumor differentiation and worse patient survival in thyroid [32], prostate [33], and hepatobiliary cancers [34,35]. Taken together, our findings suggest that Aurora B overexpression serves as a useful marker predicting ETR and hence poor prognosis.…”
Section: Discussionsupporting
confidence: 90%
“…Univariable analysis showed high AURKB and GMNN PI to be associated with a significantly worse prognosis in terms of OS and EFS, in agreement with publicly available NB gene expression array data (R2: microarray analysis and visualization platform (http://r2.amc.nl)). Our data are also in line with studies that showed an association between increased immunohistochemical expression of AURKB and shorter survival in head and neck [31], laryngeal [32], lung [33], hepatocellular [34], biliary tract [35], endometrial [36], and ovarian cancer [37]. Similarly, our results are consistent with association between high GMNN level and shorter survival in breast [38], penile [39], renal cell [40], and other cancers, reviewed by Kapoor [41] and Petropoulou et al [20].…”
Section: Discussionsupporting
confidence: 92%
“…Some studies demonstrated that serum antip53 antibodies could be used as early markers for malignant tumors or markers for poor prognosis [21]. Activated p53 can elicit several different cellular responses, including growth arrest, senescence, and apoptosis [22].…”
Section: Discussionmentioning
confidence: 99%